Efektivitas Konseling Individual dengan Teknik Cognitiven Restructuring untuk Mereduksi Perilaku Menarik Diri pada Mahasiswa - Jumadilla Afifah; Fadhilla Yusri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Interpersonal problems within peer groups often become serious obstacles to the psychological and academic development of college students. This study aims to empirically examine the effectiveness of individual counseling services using cognitive restructuring techniques in reducing withdrawal behavior among college students experiencing peer conflict. The research method employed is a quantitative experiment with a Single-Subject Design approach, specifically utilizing an A-B design. The research subject was a 6th-semester female college student, initialized as N, who experienced cognitive distortions in the form of feelings of exclusion by her five-member peer group, which triggered acute social withdrawal behavior (isolating herself in her boarding house). Data collection was conducted through a validated withdrawal behavior scale instrument, supported by clinical observations and in-depth interviews during the baseline phase (A) and the intervention phase (B). The results of the visual analysis within-conditions and between-conditions indicated a significant decrease in withdrawal behavior scores after the implementation of 4 intervention sessions. The subject was able to identify negative automatic thoughts (arbitrary inference), replace them with rational mindsets (positive thinking), feel more relieved, and commit to self-improvement. The implications of this study prove that individual counseling with cognitive restructuring techniques can be an effective intervention strategy for campus counselors to overcome cognitive distortions and interpersonal communication barriers in college students.